Influenced of granite aggregates macrotextures on pavement skid resistance / Azura Ahmad, Mohd Hisbany Mohd Hashim and Juraidah Ahmad - Ahmad, Azura (2006)
Skid resistance is an important feature of road pavement. Concern on road safety contributes towards many researches in the relationship between road materials and skid resistance. The quality of the road material such as the aggregates is very important in affecting the resistance to skid. The current research focuses on the evaluation of physical properties of granite aggregates collected on the northern region of Peninsular Malaysia namely from the state of Perak and Penang. The study aims to investigate the correlation between PSV of granites aggregates to its mineral, texture and grain sizes. The research is also intended to study the relationship between macro-textures and PSV of aggregates in pavement skid resistance. Hence, in order to achieve the objectives of the study several basic properties test for aggregates was conducted. The basic tests that were carried out include Los Angeles Abrasion Test, Aggregates Impact Value Test, Aggregates Crushing Value Test, Flakiness Index Test, and Specific Gravity Test. PSV and Petrographic tests were carried out to achieve the main objectives. Los Angeles abrasion test for all quarries has values of less than 45% which is acceptable according to standards. Aggregate Impact Values and Aggregates Crushing Values also give a positive result which is suitable to be used in road construction. The petrographic test confirms the material used in the study is granite. The results of texture depth show some indicator of lower adequacy for road construction requirement. The skid resistance of a wide range of dry surfaces is high and fairly constant.